Charles Laselle Jamison - LeBreton, Preston P. (Academy of Management Journal, 1960)
Pays tribute to Professor Charles Adelle Jamison, founder of the Academy of Management. Educational and professional background; Writings of Jamison; Contributions in business management and research.